(untitled) (Bangladesh Agronomy Journal, 2025)
An experiment was carried out at the Agronomy field of Sher-e-Bangla Agricultural University during the period from October 2021 to March 2022 with two factors, Factor A: Sunflower varieties(2): Viz., V1= BARI Surjumukhi-2 and V2 = BARI Surjumukhi-3; and Factor B: Application of different combination of organic and inorganic manures (5): Viz, F1= Recommended dose of all chemical fertilizer (RDCF), F2= Cowdung @ 10 t ha−1 + 75% of RDCF, F3= Cowdung @ 10 t ha−1 + 50% of RDCF, F4= Poultry litter @ 5 t ha−1 + 75% of RDCF, F5= Poultry litter @ 5 t ha−1 + 50% of RDCF, F6= Vermicompost @ 5 t ha−1 + 75% of RDCF and F7= Vermicompost @ 5 t ha−1 + 50% of RDCF to investigate the effect of different combinations of organic and inorganic fertilizer for maximizing yield and oil content of sunflower. The experiment was followed the Randomized complete block design (RCBD) with three replications. Results indicated that sunflower var. BARI Surjumukhi-2 consistently outperformed BARI Surjumukhi-3. The interaction effects revealed that BARI Surjumukhi-2 interaction with Vermicompost @ 5 t ha−1 + 75% of RDCF (V1F6) achieved the highest overall performance, with values such as head diameter (18.66 cm), number of seeds per head (437.23), 1000-seed weight (62.86 g), seed yield (2.87 t ha−1), stover yield (7.86 t ha−1), harvest index (26.82%), and seed oil content (40.77%). While the interaction of BARI Surjumukhi-3 with Cowdung @ 10 t ha−1 + 50% of RDCF resulted in the lowest values. Bangladesh Agron. J. 2024, 27(1): 29-39